SKRINING KESEHATAN (HIPERTENSI, DIABETES MEILITUS, KOLESTROL DAN ASAM URAT) PADA USIA LANJUT DI KECAMATAN NEGLASARI KOTA TANGERANG: SKRINING KESEHATAN (HIPERTENSI, DIABETES MEILITUS, KOLESTROL DAN ASAM URAT) PADA USIA LANJUT DI KECAMATAN NEGLASARI KOTA TANGERANG - Afrilia, Eka; Lestari, Murni; Musa, Siti Mardhatillah (Ruang Ide Publisher, 2023)
Aging is the process of becoming old and is the final stage of human development that begins at the age of 60. Aging is not a disease, but a gradual process that results in cumulative changes leading to a decline in the body's ability to withstand stimuli from within and outside the body, ending in death. One problem in Neglasari District, Tangerang City is the lack of knowledge among the elderly about early health screening, resulting in a high prevalence of non-communicable diseases such as hypertension, diabetes mellitus, uric acid, and cholesterol. Based on this problem, the Faculty of Health Sciences, through a community service team, carried out early detection of non-communicable diseases in the elderly and provided education using leaflets. The government has also launched services for the elderly in order to improve their health status. The sample size was 23 elderly people. Regular health check-ups are useful for determining an individual's health status and for early detection of potentially harmful diseases or symptoms. Keywords: Elderly, Educational, Screening